New records and five new species of sipunculans (Sipuncula) from the central and northwestern Mexican Pacific - Gómez-Vásquez, Julio D. (European Journal of Taxonomy, 2024)
Sipuncula are marine unsegmented worms that can be found in benthic habitats, from shallow to deep-sea waters. In Mexico these worms have been scarcely studied. Among nine studies in the entire Mexican Pacific coasts, seven are from the central and northwestern Mexican Pacific. For over 80 years, only 24 species have been recorded. To improve the knowledge of the sipunculans from the central and northwestern Mexican Pacific, 501 specimens from three scientific collections of Mexico were revised. The specimens were collected by diverse methods from intertidal, subtidal, and bathyal depths ( 1000 m), from 27 locations along the central and northwestern Mexican Pacific. Sixteen taxa belonging to nine genera and five families were identified. One species is recorded for the first time in the Mexican Pacific and five new species are described, one from intertidal and shallow subtidal depths: Phascolosoma (Phascolosoma) azteca sp. nov.; two from subtidal depths: Phascolion (Lesenka) salgadoi sp. nov. and Sipunculus (Sipunculus) bastidai sp. nov.; and two from bathyal depths: Apionsoma (Apionsoma) silviae sp. nov. and Apionsoma (Edmondsius) hendrickxi sp. nov. Table 1 species list. Antillesomatidae Kawauchi, Sharma & Giribet, 2012 Antillesoma mexicanum Silva-Morales et al, 2019 Panteón Beach, Oaxaca Steinbeck & Ricketts (1941) Aspidosiphonidae Baird, 1868 Aspidosiphon (Akrikos) cf. albus Murina, 1967 – Salazar-Vallejo (1983) A (A.) albus Murina, 1967 Q Cuba Hermoso-Salazar et al. (2013) A. (Aspidosiphon) elegans (Chamisso & Eysenhardt, 1821) Radack, Marshall Islands this study A. (A.) sp. – this study A. (Paraspidosiphon) pastori Silva-Morales & Gómez- Vásquez, 2021 Panteón Beach, Oaxaca this study Golfingiidae Stephen & Edmonds, 1972 Golfingia (Golfingia) cf. muricaudata (Southern, 1913) – this study Nephasoma (Nephasoma) eremita (Sars, 1851) Q NE Norway Fisher (1952) N. (N.) diaphanes (Gerould, 1813) Q E North America Gálvez-Zefrino et al. (2020) N. (N.) laetmophilum Fisher, 1952 San Diego, CA Gálvez-Zefrino et al. (2020) N. (N.) wodjanizkii wodjanizkii (Murina, 1973) Okhotsk Sea, Russia Gálvez-Zefrino et al. (2020) Onchnesoma st. steenstrupii Koren & Danielssen, 1876 Q Bergen, Norway Hermoso-Salazar et al. (2013) Phascolion (Lesenka) salgadoi sp. nov. Guaymas, Sonora this study P. (Phascolion) strombus (Montagu, 1814) Q Devonshire, England Gálvez-Zefrino et al. (2020) Themiste (Themiste) cf. blanda (Selenka et al., 1883) Japan this study T. (T.) hennahi Gray, 1828 Perú Fisher (1952) T. (T.) pyroides (Chamberlin, 1919) Laguna Beach, CA Fisher (1952) Phascolosomatidae Stephen & Edmonds, 1972 Apionsoma (Apionsoma) hespera (Chamberlin, 1920) Laguna Beach, CA Steinbeck & Ricketts (1941) A. (A.) silviae sp. nov. N Gulf of California this study A. (Edmondsius) pectinatum (Keferstein, 1867) Pacific Panama Fisher (1952) A. (E.) hendrickxi sp. nov. N Gulf of California this study Phascolosoma (Phascolosoma) agassizii Keferstein, 1866 Mendocino, CA Steinbeck & Ricketts (1941) P. (P.) perlucens Baird, 1868 Q Jamaica Fisher (1952) P. (P.) puntarenae Grübe & Örsted in Grübe, 1858 Puntarenas, Costa Rica Fisher (1952) Phascolosoma (P.) azteca sp. nov. Los Arcos, Jalisco this study Sipunculidae Rafinesque, 1814 Sipunculus (S.) bastidai sp. nov. W Baja California this study Sipunculus (S.) nudus Linnaeus, 1766 Q “European waters” Steinbeck & Ricketts (1941) Xenosiphon branchiatus (Fischer, 1894) Ecuador Fisher (1947)
Annelidabase. Article is open access.